Tropical butterflies use thermal buffering and thermal tolerance as alternative strategies to cope with temperature increase - Ashe-Jepson, Esme; Arizala Cobo, Stephany; Basset, Yves; Bladon, Andrew J; Kleckova, Irena; Laird-Hopkins, Benita C; Mcfarlane, Alex; Sam, Katerina; Savage, Amanda F; Zamora, Ana Cecilia; Turner, Edgar C; Lamarre, Greg P A (The Journal of animal ecology, 2023)
Climate change poses a severe threat to many taxa, with increased mean temperatures and frequency of extreme weather events predicted. Insects can respond to high temperatures using behaviour, such as angling their wings away from the sun or seeking cool local microclimates to thermoregulate or through physiological tolerance. In a butterfly community in Panama, we compared the ability of adult butterflies from 54 species to control their body temperature across a range of air temperatures (thermal buffering ability), as well as assessing the critical thermal maxima for a subset of 24 species. Thermal buffering ability and tolerance were influenced by family, wing length, and wing colour, with Pieridae, and butterflies that are large or darker in colour having the strongest thermal buffering ability, but Hesperiidae, small, and darker butterflies tolerating the highest temperatures. We identified an interaction between thermal buffering ability and physiological tolerance, where species with stronger thermal buffering abilities had lower thermal tolerance, and vice versa. This interaction implies that species with more stable body temperatures in the field may be more vulnerable to increases in ambient temperatures, for example heat waves associated with ongoing climate change. Our study demonstrates that tropical species employ diverse thermoregulatory strategies, which is also reflected in their sensitivity to temperature extremes.
Keywords: Climate Change; Hot Temperature; Temperature; motýli; critical thermal maximum; Animals; insect; butterfly; nízká teplota; thermal limits; Body Temperature Regulation; Lepidoptera; zvířata; Butterflies; termoregulace; klimatické změny; vysoká teplota; Cold Temperature; ectotherm; buffering ability; teplota; thermal ecology